A survey of Phrurolithidae (Arachnida: Araneae) in southern Caucasus, Iran and Central Asia - Zamani, Alireza; Marusik, Yuri M. (Zootaxa, 2020)
The spider family Phrurolithidae is revised in Azerbaijan, Iran and Tajikistan. The new genus Bosselaerius gen. n. is described to encompass three species: B. hyrcanicus sp. n. (type species, ♂ ♀, Azerbaijan, Iran), B. tajikistanicus sp. n. (♀, Tajikistan) and B. daoxianensis (Yin, Peng, Gong & Kim, 1997) comb. n. (♂, China). Furthermore, a new species of Phrurolithus C.L. Koch, 1839, namely P. azarkinae sp. n. (♂ ♀, Azerbaijan, Iran) is described, a redescription is provided for the poorly-known P. luppovae Spassky, 1941 (♂, Tajikistan), with its female being described for the first time, and P. pullatus Kulczyński, 1897 is recorded in Iran for the first time, representing the easternmost recorded locality for this species. Finally, 27 species of Chinese Phrurolithidae currently classified in Phrurolithus are transferred to Otacilia Thorell, 1897 on the basis of somatic characters and the morphology of the copulatory organs. Distributions of all treated species are mapped.